2020
DOI: 10.3897/zookeys.1003.56557
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic revision of the Afrotropical hover fly genus Senaspis Macquart (Diptera, Syrphidae)

Abstract: The representatives of the Afrotropical hover fly genus Senaspis Macquart (Diptera) are revised. In total, ten species are recognized. Senaspis apophysata (Bezzi) is herewith placed as junior synonym of S. flaviceps Macquart, S. livida (Bezzi) is herewith placed as junior synonym of S. dentipes (Macquart) and S. griseifacies (Bezzi) is herewith placed as junior synonym of S. haemorrhoa (Gerstaecker). All species are redescribed and an identification key is provided. DNA barcoding analysis (7 species, 64 barcod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Moreover, the morphological differences between these two genera are subtle, such that it is not possible to unambiguously separate both sexes of all species. De Meyer et al (2020a, 2020b) showed that eye morphology of males from P. melas and Phytomia poensis (i.e., the P . melas species‐group) was slightly deviant from other Phytomia species, possibly reflecting transitional changes between the holoptic Phytomia and the dichoptic Simoides .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the morphological differences between these two genera are subtle, such that it is not possible to unambiguously separate both sexes of all species. De Meyer et al (2020a, 2020b) showed that eye morphology of males from P. melas and Phytomia poensis (i.e., the P . melas species‐group) was slightly deviant from other Phytomia species, possibly reflecting transitional changes between the holoptic Phytomia and the dichoptic Simoides .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the morphological differences between these two genera are subtle, such that it is not possible to unambiguously separate both sexes of all species. De Meyer et al (2020aMeyer et al ( , 2020b showed that eye morphology of males from P. melas and Phytomia poensis (i.e., the P. melas speciesgroup) was slightly deviant from other Phytomia species, possibly reflecting transitional changes between the holoptic Phytomia and the dichoptic Simoides. As suggested by De Meyer et al (2020b) on the basis of preliminary tree reconstructions, Phytomia and Simoides cannot be maintained as separate entities and that the morphological differences between both genera (i.e., holoptic eyes in male Phytomia, dichoptic eyes in male Simoides) at least have evolved twice.…”
Section: Intrageneric Relationships In the Genus Mesembriusmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) dragonfly wing [88]. (d) honeybee wing [89] Aerodynamic theories in conventional aircraft are not sufficiently able to elucidate the principles of insect flight. However, prior studies have revealed how insects with flapping wings can produce large aerodynamic forces [7][8][9].…”
Section: List Of Figuresmentioning
confidence: 99%
“…Indeed, Whittington (2003) in his assessment of the Afrotropical syrphid fauna points out that the taxonomy of most of the Afrotropical hover fly genera is poorly known and that generic identification keys are largely incomplete. However, in recent years, the number of taxonomic studies on the group is increasing with new identification keys for a number of genera, including Afrosyrphus Curran, 1927 ( Mengual et al 2020 ), Ceriana Rafinesque, 1815 ( Thompson 2013 ), Chasmomma Bezzi, 1915 ( Kassebeer 2000 ), Eristalinus Rondani, 1845 (subgenus Merodonoides ) ( Thompson 2019 ), Megatrigon Johnson, 1898 ( Doczkal et al 2016 ), (part of) Merodon Meigen, 1803 ( Radenković et al 2018 ), Phytomia Guérin-Méneville, 1834 ( De Meyer et al 2020a ), Senaspis Macquart, 1850 ( De Meyer et al 2020b ), Syritta Le Peletier & Serville, 1828 ( Lyneborg and Barkemeyer 2005 ) and Spheginobaccha de Meijere, 1908 ( Thompson and Hauser 2015 ). Nevertheless, gaps in our taxonomic knowledge of several other genera remain ( Ssymank et al in press ), the genus Mesembrius Rondani, 1857 being one of them.…”
Section: Introductionmentioning
confidence: 99%